DESIGNING AND STANDARDIZING A TEST FOR COURT DEFENSE AGAINST ATTACKS (SPIKE) FOR PREMIER LEAGUE VOLLEYBALL PLAYERS - Asst. Prof. Dr. Amjad Hamed Badr (Scholars Digest Publishing, 2025)
Research Objectives: 1. Design a test for court defense against attacks (spike) for Premier League volleyball players. 2. Standardize the test for court defense against attacks (spike) for Premier League volleyball players. 3. Establish standardized performance levels that can be used to assess the efficiency of front-row players in court defense after executing a spike. The researcher employed the descriptive survey method due to its suitability for the nature of the study. The research population consisted of 128 Premier League volleyball players, with a sample size of ninety-four players selected from six clubs. The researcher designed and standardized the test following scientifically recognized procedures for test design and standardization. Data was processed using SPSS to achieve the study's objectives. Findings: • The test for court defense against attacks (spike) for Premier League volleyball players was successfully designed and standardized. • Norm-referenced scores and performance levels for the test were established. • The test effectively evaluates the accuracy of court defense against spike attacks for all Premier League volleyball players.
Keywords: Standardization, Court Defense Test, Spike, Premier League Players, Volleyball.